Getting Along Without Regulation Q: Testing the Standard View of Deposit- Rate Competition During the "Wild-Card Experience" - Kane, Edward J. (Journal of Finance, 1978)
Edward J. Kane, Getting Along Without Regulation Q: Testing the Standard View of Deposit- Rate Competition During the "Wild-Card Experience", The Journal of Finance, Vol. 33, No. 3, Papers and Proceedings of the Thirty-Sixth Annual Meeting American Finance Association, New York City December 28-30, 1977 (Jun., 1978), pp. 921-932